Tandem mass tag-based proteomics technology provides insights into multi-targeted mechanism of peptide MOp2 from Moringa oleifera seeds against Staphylococcus aureus. (15th March 2023) - Huang, Zhiyuan; Dong, Wenming; Fan, Jiangping; Tian, Yang; Huang, Aixiang; Wang, Xuefeng
Abstract: Our previous study proved that the peptide MOp2 from Moringa oleifera seeds exhibited membrane-damaging effects on Staphylococcus aureus . In this study, TMT-based proteomics technology was mainly used to investigate the antimicrobial mechanism of MOp2 against S. aureus . A total of 541 differentially expressed proteins (DEPs) were identified in S. aureus treated with MOp2, among which 256 and 285 DEPs were upregulated and downregulated, respectively. They were mainly involved in inositol phosphate metabolism, S. aureus infection, citrate cycle (TCA cycle), and phosphotransferase system (PTS) and acted as ABC transporters and ribosomes. Moreover, the decreasing AKP activity indicated that MOp2 affected cell wall biosynthesis, and excessive ROS accumulation caused apoptosis, resulting in DNA fragmentation, nuclear morphological changes, and phosphatidylserine externalization. Additionally, molecular docking showed that MOp2 could interact with eight DEPs, including ProC, QoxB, SOD2, DnaK, GroEL, RplY, AcpS, and FabG, indicating that MOp2 might act on these molecular targets, leading to increased cell permeability, oxidative damage, impaired protein synthesis, cell wall synthesis obstruction, and energy metabolism disorder. Overall, these findings provided new insights into the multi-targeted mechanism of MOp2 against S. aureus, and could provide a theoretical basis for its application as a novel food preservative and antibiotic substitute. Graphical abstract: Image 1 Highlights: Multi-targeted mechanism of MOp2 against Staphylococcus aureus was investigated. A total of 541 differentially expressed proteins were identified in S. aureus treated with MOp2. MOp2 could increase ROS accumulation, resulting in S. aureus apoptosis. Molecular docking showed that MOp2 may act on eight protein targets in S. aureus.